Provision of Legal Assistance to the Poor by Legal Assistance Institutions by Free Way in Demak Regency - Edy Lisdiyono; Setiyowati (Community Service Journal of Law, 2022)
The provisions of legal aid for the poor who are in conflict with the law by the Legal Aid Institute had been regulated by the provisions of Government Regulation Number 42 of 2013 concerning Terms and Procedures for Providing Legal Aid and Distribution of Legal Aid Funds, the Regulation of the Minister of Law and Human Rights Number 3 of 2013 concerning Procedures for Verification and Accreditation of Legal Aid Institutions, and the Decree of the Ministry of Law and Human Rights of the Republic of Indonesia Number M.HH-03.HN. 03.03 of 2013 concerning the Amount of Litigation and Non-Litigation Legal Aid Fees. Legal aid for the poor with this free system has conditions that must be met. They are really incapable, and there is a certificate from the local/village head that the person concerned is really incapable which is in accordance with the law. There was a problem occurred in Jepara Regency that there were still few accredited Legal Aid Institutions, and there were quite a lot of poor people who were in conflict with the law so that there was an imbalance between legal aid service personnel and the cases at hand. From the data obtained after being analyzed that in Jepara Regency, the legal aids for the people who were in conflict with the law for free were still not evenly distributed because legal aid assistants were not proportional to the number of cases faced by the people who were in conflict with the law. There were very few aid accredited by the Ministry of Law and Human Rights. Furthermore, if the community deals with unaccredited legal assistance, in this case, they will not receive financial assistance from the State in providing assistance.